Physical properties of epitaxial SrMnO2.5−δFγ oxyfluoride films. (19th June 2019) - Wang, Jiayi; Shin, Yongjin; Gauquelin, Nicolas; Yang, Yizhou; Lee, Christopher; Jannis, Daen; Verbeeck, Johan; Rondinelli, James M; May, Steven J
Abstract: Recently, topotactic fluorination has become an alternative way of doping epitaxial perovskite oxides through anion substitution to engineer their electronic properties instead of the more commonly used cation substitution. In this work, epitaxial oxyfluoride SrMnO2.5− δ F γ films were synthesized via topotactic fluorination of SrMnO2.5 films using polytetrafluoroethylene as the fluorine source. Oxidized SrMnO3 films were also prepared for comparison with the fluorinated samples. The F content, probed by x-ray photoemission spectroscopy, was systematically controlled by adjusting fluorination conditions. Electronic transport measurements reveal that increased F content (up to γ   =  0.14) systematically increases the electrical resistivity, despite the nominal electron-doping induced by F substitution for O in these films. In contrast, oxidized SrMnO3 exhibits a decreased resistivity and conduction activation energy. A blue-shift of optical absorption features occurs with increasing F content. Density functional theory calculations indicate that F acts as a scattering center for electronic transport, controls the observed weak ferromagnetic behavior of the films, and reduces the inter-band optical transitions in the manganite films. These results stand in contrast to bulk electron-doped La1− x Ce x MnO3, illustrating how aliovalent anionic substitutions can yield physical behavior distinct from A -site substituted perovskites with the same nominal B -site oxidation states.